The seventy prepositions : poems - Snow, Carol, 1949- (New California poetry., 2004)
Carol Snow's award-winning poetry has been admired and celebrated as ""work of difficult beauty"" (Robert Hass), ""ever restless, ever re-framing the frame of reference"" (Boston Review), teaching us ""how brutally self-transforming a verbal action can be when undertaken in good faith"" (Jorie Graham). In this, her third volume, Snow continues to mine the language to its most mysterious depths and to explore the possibilities its meanings and mechanics hold for definition, transformation, and emotional truth. These poems place us before, and in, language--as we stand before, and in, the world